THE EFFECT OF PHYSICAL BULLYING BEHAVIOR ON MOTIVATION AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Faisal Anwar; Dian Aswita; Nurfarah Idayu (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
This research aimed to specify the influence of physical bullying behavior on the motivation and learning outcomes of elementary school students in Banda Aceh, Indonesia. The approach used was a quantitative method with ex post facto. The samples were 100 students of SD Negeri 53 Banda Aceh. Data collection was conducted by using questionnaires, interviews, and documentation. The technique of data analysis was conducted by a t-test. The results of the data analysis of physical bullying behavior on learning motivation obtained at the value of 2.834 and table of 2,04841, so that t count > t table and judging from the level of significance, the variable physical bullying behavior had a value of 0.008 < 0.05, while the results Data analysis of physical bullying behavior on student learning outcomes obtained t-count value of 11.212 and t-table of 2.04841, so that t-count > t-table and seen from the level of significance, the variable value of physical bullying behavior was 0.000 <0.05. Based on the data obtained, the results of this study concluded it can be concluded that physical bullying behavior affects the motivation and learning outcomes of SD Negeri 53 Banda Aceh students.